THE VILLALBETO DE LA PEñA METEORITE FALL: II. DETERMINATION OF ATMOSPHERIC TRAJECTORY AND ORBIT - Trigo-Rodríguez J.M.; Llorca J.; Borovička J.; Spurný P.; Ortiz J.L.; Castro-Tirado A.J.; Docobo J.A. (My University, 2006)
The L6 ordinary chondrite Villalbeto de la Peña fall occurred on January 4, 2004, at 16:46: 45 ± 2 s UTC. The related daylight fireball was witnessed by thousands of people from Spain, Portugal, and southern France, and was also photographed and videotaped from different locations of León and Palencia provinces in Spain. From accurate astrometric calibrations of these records, we have determined the atmospheric trajectory of the meteoroid. The initial fireball velocity, calculated from measurements of 86 video frames, was 16.9 ± 0.4 km/s. The slope of the trajectory was 29.0 ± 0.6° to the horizontal, the recorded velocity during the main fragmentation at a height of 27.9 ± 0.4 km was 14.2 ± 0.2 km/s, and the fireball terminal height was 22.2 ± 0.2 km. The heliocentric orbit of the meteoroid resided in the ecliptic plane (i = 0.0 ± 0.2°), having a perihelion distance of 0.860 ± 0.007 AU and a semimajor axis of 2.3 ± 0.2 AU. Therefore, the meteorite progenitor body came from the Main Belt, like all previous determined meteorite orbits. The Villalbeto de la Peña fireball analysis has provided the ninth known orbit of a meteorite in the solar system. © The Meteoritical Society, 2006.